Time as a Determinant of Comparative Advantage - Li, Yue; Wilson, John S. (2012)
It is assumed that added time to export adds cost to and lowers the volume of trade. Time delays may also affect the composition of trade and can disproportionately reduce trade in time-sensitive goods. This paper investigates the validity of these propositions using the World Bank Doing Business database and Enterprise Surveys for 64 developing countries. The authors find that in countries where there is longer time needed to export firms in time-sensitive industries are less likely to become exporters. Moreover, firms that do export have lower export intensities. Their findings imply that time to export is a significant determinant of comparative advantage. For example, consider two industries that have the same export probability and intensity - but differ in time-sensitivity by one standard deviation. Action taken to cut time to export by 50 percent for one industry opens a 6 percentage point difference between the export probabilities of the two industries. In addition, steps to cut time delays increase export intensities by 1.9 percentage points. This impact applies to industries with different productivity levels -- and those in developing countries with different income levels.